Anaesthetic management of a parturient with cyclical thrombocytopenia. Issue 1 (2nd February 2018) - Katz, Richard; McCaul, Conan; Kininy, Norhan El; Quinn, John
Summary: Cyclical thrombocytopenia is a rare idiopathic haematological condition characterised by cyclical fluctuations in platelet counts resulting in episodes of severe thrombocytopenia. The precise pathogenesis and optimal therapy for this condition have yet to be identified, making the management of the obstetric patient with cyclical thrombocytopenia challenging. The uncontrolled disease process on the haemostatic system affected not only our ability to provide safe neuraxial analgesia to a parturient, but also placed our patient at a significantly increased risk of major obstetric haemorrhage throughout her pregnancy. Her delivery plan included induction of labour at term, coinciding with one of her peaks in platelet count, avoidance of neuraxial analgesia and early surgical intervention if there was evidence of a postpartum haemorrhage. Due to the potential risk of foetal thrombocytopenia, fetal blood sampling and the use of fetal scalp electrodes were avoided. A healthy baby was delivered following an uneventful normal vaginal delivery.